Maqasid Al-Shariah and Artificial Intelligence: Unaddressed Issues in Contemporary AI Ethics Studies - Prabowo, Yuga Bayu; Ervani, Dilfam Adisya; Archningtia, Putri Dwi (IDRIS Darulfunun Institute, 2026)
The rapid advancement of Artificial Intelligence (AI) has intensified ethical debates within contemporary technology studies. Nevertheless, current AI ethics discourse remains predominantly shaped by Western philosophical paradigms such as utilitarianism, deontology, and virtue ethics, which often overlook moral, social, and spiritual dimensions central to non-Western societies, including Islamic ethical traditions. This study aims to map contemporary AI ethics scholarship, critically examine Islamic ethical responses to AI, and develop an evaluative framework grounded in Maqasid al-Shariah. Using a qualitative approach with a Systematic Literature Review (SLR) design, this research analyzes peer- reviewed publications from the last decade drawn from major academic databases. Data analysis is conducted through thematic analysis, comparative analysis, and conceptual synthesis. The findings reveal that Islamic AI ethics studies are still dominated by normative and declarative approaches, with limited operationalization of Maqasid al-Shariah as an evaluative tool, and a notable absence of integrative models connecting Islamic ethics with global AI ethics frameworks. This study contributes theoretically by positioning Maqasid al- Shar??ah as a holistic, value-based, and applicable ethical framework for assessing AI in relation to justice, public welfare, and the protection of human dignity within a global technological context.